IRCAS-SOFRI project : Development of new technologies for control of citrus huanlongbing in Southeast Asia (Japan, 2004)
List of content: Citrus huanlongbing disease in Vietnam and its control measures; Practical strategies for research and technology dissemination for citrus HLB control; Integrated management of citrus huanlongbing disease in Indonesia, japan, cambodia; and development of new technologies for control of citrus huanglongbing in Southeast Asia.
Keywords: Huanglongbing,Citrus fruits; Citrus; Southeast Asia